Flagship 1: Technological innovation and sustainable intensification - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Foresight modeling for climate change, new technologies, and shifts in demand ● Policy options, investment, and regulatory reform to support agricultural innovation ● New approaches to meeting farmers’ needs for information